2020
DOI: 10.1159/000512620
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Review of Choroidal Involution in Eyes with Retinopathy of Prematurity Treated with Bevacizumab

Abstract: Purpose: Retinopathy of prematurity (ROP) is considered a disease of the inner retina; however, there is increasing evidence that demonstrates choroidal vasculature loss in ROP, leading to degeneration of outer retinal function and visual deterioration. Central choroidal thinning is noted in children with history of ROP using optical coherence tomography (OCT) imaging. This study characterizes the presence and persistence of choroidal loss angiographically in eyes of infants treated with intravitreal bevacizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…al., the presence of choroidal hypo uorescence in the central and or peripheral retina of ROP patients was demonstrated(19).Consistent with previous studies, we found that choroidal involution is associated with the presence of pre-plus/plus, not with the ROP stage.According to our data, the choroidal vascularity index (CVI) and choroidal stromal index (CSI) weren't signi cantly different in the treatment and untreated groups. CVI is a novel means of choroidal evaluation introduced by Agrawal et al in 2016(12).…”
supporting
confidence: 92%
“…al., the presence of choroidal hypo uorescence in the central and or peripheral retina of ROP patients was demonstrated(19).Consistent with previous studies, we found that choroidal involution is associated with the presence of pre-plus/plus, not with the ROP stage.According to our data, the choroidal vascularity index (CVI) and choroidal stromal index (CSI) weren't signi cantly different in the treatment and untreated groups. CVI is a novel means of choroidal evaluation introduced by Agrawal et al in 2016(12).…”
supporting
confidence: 92%
“…By using OCT and fluorescein angiography, respectively, previous studies have also described altered choroidal filling patterns and decreased choriocapillaris vessel density in preterm children with and without ROP. 27,28 Children with ROP may exhibit visual acuity impairment after ROP regression despite normal macular appearance. In a study using electrophysiology, RPE degeneration and photoreceptor dysfunction were considered possible disease pathomechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This choroidal vascular loss has been proven angiographically. In a study by Islam et al, the presence of choroidal hypo fluorescence in the central and or peripheral retina of ROP patients was demonstrated [ 26 ].…”
Section: Discussionmentioning
confidence: 99%